Stakeholder mapping and evaluation of the DYTAEL 2023 action plan - Piraux, Marc; Mbaye, Bann; Ndour, Moussa; Sene, Mame Birame (2023)
Workshop report on: • Mapping agro-ecology stakeholders in the Fatick department ; • Reflecting on the DyTAEL's internal operating procedures; • Presenting and guiding two diagnostic studies to be carried out in 2024 as part of the Agroecology Initiative (innovation tracking + socio-technical diagnosis); • Evaluating the DyTAEL 2023 annual action plan in preparation for the next Steering Committee meeting;